2018
DOI: 10.3390/ijms19082293
|View full text |Cite
|
Sign up to set email alerts
|

The Micro-RNA Expression Profiles of Autoimmune Arthritis Reveal Novel Biomarkers of the Disease and Therapeutic Response

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease of the joints affecting about 0.3–1% of the population in different countries. About 50–60 percent of RA patients respond to presently used drugs. Moreover, the current biomarkers for RA have inherent limitations. Consequently, there is a need for additional, new biomarkers for monitoring disease activity and responsiveness to therapy of RA patients. We examined the micro-RNA (miRNA) profile of immune (lymphoid) cells of arthritic Lewis rats and arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 81 publications
3
42
0
Order By: Relevance
“…Most of the dysregulated miRNAs in CAP, such as miR-146a (Ichii et al 2012;Jang et al 2016;Bhardwaj 2017;Shi et al 2019), miR-96 (Dudics et al 2018), miR-423 (Wang et al 2017;Nakhjavani et al 2019) and miR-205 (Suojalehto et al 2013), their expression in various previously reported inflammatory diseases showed similar patterns to this study. It has been found that miR-146, miR-96, miR-423, and miR-205 are closely related to prostate cancer (Song et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Most of the dysregulated miRNAs in CAP, such as miR-146a (Ichii et al 2012;Jang et al 2016;Bhardwaj 2017;Shi et al 2019), miR-96 (Dudics et al 2018), miR-423 (Wang et al 2017;Nakhjavani et al 2019) and miR-205 (Suojalehto et al 2013), their expression in various previously reported inflammatory diseases showed similar patterns to this study. It has been found that miR-146, miR-96, miR-423, and miR-205 are closely related to prostate cancer (Song et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Earlier studies on animal models have also confirmed the role of mir-155 as one of the factors contributing to arthritis development. Results of serum testing in arthritic rats showed an increased level of miR-155; on the other hand, mice lacking miR-155 were resistant to collagen-induced arthritis [ 14 , 15 ]. In the present study, we decided to focus on microRNAs since they are responsible for regulating gene expression of transcriptional factors that impact Th17/Treg balance [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have shown a correlation between miR-155 and STAT3 as well as between miR-26 and STAT3, SMAD3, and SOCS1 in RA Th17 cells. Che et al have shown that miR-155 shows the potential to be used as a biomarker [ 14 ]. For RA Treg cells, we found a correlation between miR-155 with SMAD3 and SMAD4, which again confirms the possibility to use miR-155 as a biomarker [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This initiates both a B and T cell response to CII, leading to arthritis induction [ 32 , 33 ]. Another commonly used model is the adjuvant-induced arthritis (AA) model [ 34 , 35 ]. In AA, Lewis rats are immunized with heat-killed Mycobacterium tuberculosis H 37 R a (Mtb) emulsified in mineral oil.…”
Section: Animal Models Of Ra For Studying Disease Pathogenesis Andmentioning
confidence: 99%